2004
DOI: 10.1093/jhered/esh066
|View full text |Cite
|
Sign up to set email alerts
|

Eurasian Otters, Lutra lutra, Have a Dominant mtDNA Haplotype From the Iberian Peninsula to Scandinavia

Abstract: The Eurasian otter, Lutra lutra, has a Palaearctic distribution and has suffered a severe decline throughout Europe during the last century. Previous studies in this and other mustelids have shown reduced levels of variability in mitochondrial DNA, although otter phylogeographic studies were restricted to central-western Europe. In this work we have sequenced 361 bp of the mtDNA control region in 73 individuals from eight countries and added our results to eight sequences available from GenBank and the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 18 publications
1
48
1
Order By: Relevance
“…Two hundred and ninety-nine base pairs of sequence from the 5 0 end of the mtDNA CR from the 58 samples in this study was aligned with equivalent European otter sequences derived by Mucci et al (1999), Cassens et al (2000), Ferrando et al (2004) and Perez-Haro et al (2005) using DAMBE v4.2.13 (Xia and Xie 2001). All samples (n = 357) were then analyzed to give a description of the distributions of known European otter CR haplotypes across Europe.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two hundred and ninety-nine base pairs of sequence from the 5 0 end of the mtDNA CR from the 58 samples in this study was aligned with equivalent European otter sequences derived by Mucci et al (1999), Cassens et al (2000), Ferrando et al (2004) and Perez-Haro et al (2005) using DAMBE v4.2.13 (Xia and Xie 2001). All samples (n = 357) were then analyzed to give a description of the distributions of known European otter CR haplotypes across Europe.…”
Section: Methodsmentioning
confidence: 99%
“…Within Europe, Mucci et al (1999) identified two haplotypes, Perez-Haro et al (2005) identified three and Cassens et al (2000) and Ferrando et al (2004) identified five each. Haplotypes in these studies are often the same and the haplotype variously designated DK/Lut1/H1 has repeatedly been found to be the most common, although a second-UK/Lut3/H4 was identified as the most common in East Germany (Cassens et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, phylogeographic studies conducted on Mustelidae are few and mostly inconclusive. The study of Davison et al (2001) on Martes martes and Mustela putorius and the work of Ferrando et al (2004) on Lutra lutra showed a lack of structuring and ancient lineages explained by an expansion from a single, but not localized, European refugium. For M. erminea, low genetic differentiation and structure were observed among continental Eurasian populations, with only one lineage from Europe (Ireland excepted) to Japan up to Alaska whose origin is not specified (Fleming and Cook, 2002;Kurose et al, 2000Kurose et al, , 2005Martinkova et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…great bustard (Otis tarda; Pitra et al 2000)). In contrast, little population structure has been detected in some widespread species, such as otters (Lutra lutra; Ferrando et al 2004) and several avifauna species (e.g. great spotted woodpecker (Dendrocopos major; Zink et al 2002), common sandpiper (Actitis hypoleucos; Zink et al 2008), and Eurasian magpie (Pica pica; Zhang et al 2012)).…”
Section: Introductionmentioning
confidence: 99%